Improving customer loyalty through customer experience, price attractiveness, and customer relationship management - Suganda, Uce Karna; Priadi, Yudi (Jurnal Manajemen Industri dan Logistik, 2023)
This study aims to determine the effect customer Experience, Price Attractiveness and Customer Relationship Management have on Customer Loyalty. The data is collected using primary sources, which is done by distributing questionnaire to 300 respondents using purposive sampling technique. The findings show that customer experience is perceived as good, price attractiveness is perceived as attractive and affordable, while customer loyalty is not high. there is a significant influence of Customer Experience on Customer Loyalty (R2 = 0.31). Customer experience is related to customer loyalty, because the experience of a brand involves the subjective experience and behavior of a consumer. Price attractiveness has a greater effect on customer experience and Customer Relationship Management. Customer Relationship Management and price attractiveness have a positive influence on customer loyalty. Customer experience has a positive influence on customer loyalty in 'Kedai Yups' café.